Pengaruh Penerapan Insentif Pajak, Tax Literacy Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM - Nurma Risa; Ghahara Diandra Bilqis; Neneng Lasmita Susanti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to determine the effect of Tax Incentives, Tax Literacy and Tax Sanctions on MSME Taxpayer Compliance in the Bekasi City area. The number of samples used in this study were 118 respondents. The sample in this study used an accidental sampling technique which was carried out using a questionnaire distributed to respondents via google form. The results of the study found that tax literacy had a positive effect on MSME taxpayer compliance, while tax incentives and tax sanctions had no effect on MSME taxpayer compliance.